Metaforyczne wino. Językowe sposoby charakteryzowania cech wina w kontekście lingwistyki kognitywnej (Conversatoria Linguistica, 2019)
The article is going to show metaphorical language of wine tasting notes and wine tasting notes dictionaries available on Polish internet wine services. The language shows how we conceptualize wine. The analysis is conducted and based on cognitive linguistic approach, is a basis for further research and does not constitute an exhausted subject.